2018
DOI: 10.1111/cen.13544
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk factors for haemodynamic instability during pheochromocytoma surgery in Chinese patients

Abstract: HI is common among Chinese patients undergoing surgery for pheochromocytoma. Our study identified three predictive factors for intraoperative HI: a large tumour diameter, diabetes/prediabetes and a great preoperative systolic blood pressure fluctuation. Furthermore, patients are more likely to suffer from HI when they have more predictive risk factors. Identification of these risk factors can help to improve perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 38 publications
(52 reference statements)
3
40
1
Order By: Relevance
“…As confirmed in previous studies, this criteria are closely related to severe morbidity, especially cardiovascular morbidity [9,11]. In this study, 26.1% and 27.7% of patients in the development and validation cohorts, respectively, had IHD, which is consistent with a previous retrospective study that reported an incidence of IHD of 32.8% (44/134) in Chinese patients [4]. This nomogram incorporates four predictors based on extensive clinicopathological data, which were BMI, CHD, tumor size, and preoperative use of crystal/colloid fluid, for prediction of IHD.…”
Section: Fig 2 Nomogram To Predict Ihd In Patients With Pheochromocysupporting
confidence: 92%
See 1 more Smart Citation
“…As confirmed in previous studies, this criteria are closely related to severe morbidity, especially cardiovascular morbidity [9,11]. In this study, 26.1% and 27.7% of patients in the development and validation cohorts, respectively, had IHD, which is consistent with a previous retrospective study that reported an incidence of IHD of 32.8% (44/134) in Chinese patients [4]. This nomogram incorporates four predictors based on extensive clinicopathological data, which were BMI, CHD, tumor size, and preoperative use of crystal/colloid fluid, for prediction of IHD.…”
Section: Fig 2 Nomogram To Predict Ihd In Patients With Pheochromocysupporting
confidence: 92%
“…due to excessive release of catecholamines into the circulation, which may result in life-threatening situations [4,5]. Mortality rate of pheochromocytomas has been reported can be as high as 50%; however, through widespread improvements in preoperative medical preparation [PMP], anesthesia strategy and surgical techniques, it has been significantly reduced to 0-2.9% [3].…”
mentioning
confidence: 99%
“…Although the mainstay strategy for treatment of pheochromocytomas, surgery is associated with a high risk of perioperative morbidity (4). It has been reported that mortality can be as high as 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Speculation on avoiding alpha-receptor pretreatment in certain groups of patients with PPGL has been raised [4,8,[16][17][18]. However, reliable predictors of hemodynamic instability are not well characterized [11,14,[19][20][21]. This study does not have power to examine risk factors for per-operative hemodynamic instability but favours high dose PBZ pretreatment for minimizing perioperative hemodynamic variability.…”
Section: Discussionmentioning
confidence: 93%